Analisis Usaha Unggulan Bumdes Dengan Pendekatan Analytical Hierarchy Process (AHP) Di Desa Citangtu Kecamatan Pangatikan Kabupaten Garut - Yudiardi, Dodi; Pundenswari, Pupung; Novianti, Ega (Jurnal Publik, 2021)
In order to improve the economy in Indonesia, especially in villages and as a form of regional autonomy, the government issued a policy for each village to establish Village Owned Enterprises (BUMDes). Citangtu Village, is one of the areas that implemented a policy regarding BUMDes in 2015 and was established under the name "Surya Mekar Motekar". There are three business fields run by BUMDes Surya Mekar Motekar, including the trade sector with products produced in the form of goods, namely groceries, the social sector (serving) with products produced in the form of services, namely the provision of the Healthy Village program by providing recycling waste collection services for the community, and finally the rental sector with the product produced in the form of a cart rental service. The Analytical Hierarchy Process (AHP) approach in this study is used to find the potential to be developed. Based on the results of the AHP analysis of the leading business of BUMDes Surya Mekar Motekar, cart rental is the top priority with a weight value of 0.058, then basic food is the second priority with a weight value of 0.026 and Garbage Banks are the last priority with a weight value of 0.024.